The water resistance of interlocking block wall - Mohamad Aizuddin, Kamar (2015)
Water that absorbed by block will make the strength of the block decreased. When external walls are exposed to water from different sources such as rain and flood water will enter the building, travelling from outer walls into internal walls. The water may lead to cracks in bricks and lead the the building collapse. If the weather conditions did not change, it may just mean that the walls stay damp without getting the opportunity to dry out. The objectives of this proposed topic are to test compressive strength of the blocks, to study the porosity of interlocking block and most importantly, to test the water resistance of the interlocking block wall with three different conditions that is normal block wall, block wall with mortar as infill and block wall added with grout around the block. The method for porosity test,is by using vacuum saturation method. The test for block wall is by pouring the interlocking block wall with water. The porosity for normal block is with 16.03 % while for the block with mortar as infill, 10.98 %. The block wall with assemble grout around the block is the best water resistance among the three interlocking block wall. This grouted wall take 39 minutes for the water to pass through all the blocks. The poorest water resistance is normal block wall that take only 17 minutes for the water to pass through the wall. This research can conclude that the type of assemble on the interlocking block wall affected the time for the water to went through the wall.